Limits to the 2017 National Constituent Assembly from the judicial interpretation in Venezuela (Gestión y Gerencia, 2020)
This essay succinctly addresses an analysis of the constituent call made in May 2017, establishing as purpose to make a dissertation on its limits from the constituent acts’ jurisprudence set in the years 1999 and 2000. The study was done through a qualitative approach, using an hermeneutical research methodology. The conclusion was the inapplicability of the judicial precedents previously established for all the acts carried out by the 2017 Constituent Assembly.
Keywords: Constituent acts; constitutional assembly; constitutional laws; convocation; precedent